An Analysis of the Experiences of New Teachers Involved in an Induction Program: Closing the Gap between Expectations and Reality - Topp, James (Université d'Ottawa / University of Ottawa, 2018)
International literature on induction within education consistently states that induction programs provide a variety of benefits for new teachers. In Ontario in 2006, to support new teachers, the Ministry of Education introduced the New Teacher Induction Program (NTIP). The NTIP consists of three main components: an orientation for new teachers, individual mentoring for new teachers, as well as ongoing professional development opportunities tailored to new teachers. In 2006-2011, the NTIP underwent an evaluation by a research team from the University of Ottawa charged with evaluating the implementation and efficacy of the program. To date in Ontario, there is a gap in the literature on the qualitative experiences of new teachers involved in induction programs. This study, as part of the larger evaluation, sought to address the lack of empirical work in this area by presenting the lived experiences of new teachers in Ontario. Data have been generated through semi-structured interviews with 20 new teachers at the high school level in Ontario, six of whom are presented as typical cases of a range of new teacher experiences. Three existing induction programs are profiled and through an analysis of the experiences and observations of the new teachers in this study, six essential elements of induction have been described. It is anticipated that the results of this study will help inform future policy and practice in the area of induction programs.
Keywords: New Teacher Induction; Mentoring